Visual Attention Distribution According to Size, Color, and Spatial Location of Stimuli under Foveal and Peripheral Vision Conditions - Manana Khomeriki; Natela Lomashvili (European Scientific Journal, ESJ, 2025)
Visual attention allows individuals to select the information most relevant to ongoing behavior. Attention mechanisms serve two critical roles. First, attention can be used to select behaviorally relevant information and/or to ignore irrelevant or distracting information. Second, attention can modulate or enhance the selected information according to the perceiver’s state and goals. With attention, perceivers are more than passive receivers of information. They become active seekers and processors, able to interact intelligently with their environment. Among the characteristics of visual stimuli, size can refer to the spatial extent of an item. Searching for the largest item is particularly efficient. Regarding color, it has long been accepted as a pre-attentive feature.The aim of our research was to determine the importance of three characteristics of a visual object – size, color, and location in the visual field in the process of attention distribution under central and peripheral vision conditions. The study consisted of two series: in the first, the subjects performed the given task without reading any text; in the second, they performed the task while reading a running text. The study involved 40 volunteers of both sexes, aged 20 to 40 (mean age ± 32), with normal or corrected vision (visus > 0.8). All participants were right-handers and left-to-right readers. Gender distribution was balanced, and all participants were right-handed and left-to-right readers.In the no-text experiment (without additional information), when foveal information is scarce, attention distribution based on the size of the stimuli is more refined, and such stimuli are detected faster than in the text experiment (with additional information), where foveal information plays a more significant role. In both the no-text and text experiments, yellow and red stimuli are detected faster than green and blue. We assume that when perceiving a scene, the eye begins moving from the upper left corner to the lower left area, then to the lower right, and finally to the upper right during the no-text series, when focal information is scarce. Apparently, regardless of stimulus parameters and the intensity of the information flow, stimuli located in the upper left corner of the scene are perceived faster. This may be due to the habitual left-to-right reading pattern, or one can also pay attention to the phenomenon of pseudoneglect, which is often left-sided.